Cellular Behavior of Colchicum troodi Treated Primary and Metastatic Colon Adenocarcinoma Cell Lines : Colchicum troodi and Colon Cancer - Özkum Yavuz, Dudu; Becer, Eda; Vatansever, Hafize Seda; Kabadayı, Hilal; Hanoğlu, Azmi; Meriçli, Filiz; Meriçli, Ali Hikmet (Progress in Nutrition, 2021)
Colchicum troodi belongs to Colchicaceae family that particularly rich in flavonoids, phenolic acids, tannin, fatty acids and alkaloids such as colchicine. The aim of this study was to investigate the anti-proliferative and protective effects of Colchicum troodi ethanolic extract toward relevant molecular signalling pathways on Colo-320 primer and Colo-741 metastatic colon adenocarcinoma cell lines. Colchicum troodi was collected and extracted. Different concentrations of Colchicum troodi extract were incubated for 24 h and 48 h with Colo-320 and Colo-741 cells. Cell growth and cytotoxicity were measured by MTT assays. Anticancer and antiprolifetarive activities of Colchicum troodi were investigated by immunocytochemistry using antibodies directed against to -catenin, LGR5, jagged 1, IHH, CD133 and Ki-67 in Colo-320 and Colo-741 cells. In the MTT assay, 10 µg/ml and 5 µg/ml Colchicum troodi extract were found to be active against Colo-741 and Colo-320 cells, respectively. Colchicum troodi extract significantly increased caspase β-catenin immunoreactivities while IHH immunostaining intensity was decreased in Colo-741 cells. We conclude that Colchicum troodi extract increased β-catenin via Wnt/β-catenin pathway in Colo-741 cells. Interestingly, it decreased IHH immunoreactivities which is an antagonist of constitutive activity of Wnt/ β-catenin signaling and is assumed to play protective act during carcinogenesis.